THE INFLUENCE OF THE MARKETING MIX ON SHOPEE CUSTOMER SATISFACTION IN 2018 UINSU COMMUNICATIONS STUDENTS - Putri, Rizka Cantika; Alfikri, Muhammad (KABILAH : Journal of Social Community, 2022)
Abstract: The purpose of this study is to determine and describe the impact of marketing mix, product, pricing, distribution, and advertising on Shopee consumer satisfaction among UINSU Communication course students. This type of research is deductive with a quantitative approach. The survey respondent is her 45 consumers who have shopped on Shopee and are communication major students at UINSU. The analysis is multiple regression analysis. The results of this study show that the marketing mix, product, price, distribution and promotional factors have a positive impact on consumer satisfaction. However, price has the greatest impact on consumer satisfaction. From this, we can conclude that the four independent variables have a positive and significant impact on customer satisfaction, marketing mix, products, pricing, sales, and promotions. Keywords: Marketing Mix, Customer Satisfaction, Purchase Intention